ANALYSIS OF TACTICAL PROPERTIES OF MODERN GEOINFORMATIONAL MONITORING - Mikhno, O.; Patrakeyev, I.; Levinskova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
Geoinformational monitoring of urban environment is a necessary component of modern military-geographical description of military operation theater. The polymorphism property of modern geoinformational monitoring can be attributed to tactical properties, since it significantly expands range of decryption features of territory to be studied. The essence of polymorphism property of geoinformational monitoring is as follows: the same object of monitoring or the same phenomenon or process can be represented by different models. This property of geoinformational monitoring allows to preserve the integrity of representation of monitoring objects due to the invariance of description of objects and to bring the study of tasks of one type of monitoring to tasks of another type. Consistency of disparate models of monitoring objects is carried out provided that they belong to a given category of models. A constructive approach to the integration of different types of models of monitoring objects in the system of geoinformational monitoring is using methods of categorical-functional analysis. The mathematical apparatus of category theory allows the formalization of structures of complex systems in the form of sets of morphisms and objects of category of structured sets. This allows us to preserve integrity of representation of monitored object, and the consistency of its disparate models based on the analysis of their belonging to a given category of models. The paper presents the mathematical apparatus of implementation of this method, which is the theoretical basis of properties of polymorphism of geoinformational monitoring. The property of polymorphism allows us to increase the efficiency of processes of observation, evaluation, control and management of urban environment on basis of a heterogeneous polymodel complex, which forms information space of object of monitoring. Specific models of practical implementation of the polymorphism properties of geoinformational monitoring on the example of anomalous zones of density of vehicles and thermal field of the city surface are considered.